2010
DOI: 10.1017/s1368980010001163
|View full text |Cite
|
Sign up to set email alerts
|

The diet of adolescents can be improved by school intervention

Abstract: Objective: To decrease the intake of sucrose, increase the intake of fibre and the consumption of fruit and vegetables among secondary-school pupils. Design: Intervention study among eighth grade pupils during one school year. Data were collected by questionnaires and from a subgroup of pupils by 48 h dietary recall at baseline in spring 2007 and after the intervention in 2008. Setting: Twelve secondary schools were randomly allocated to intervention (IS) and control schools (CS) within three cities. Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 30 publications
4
67
0
2
Order By: Relevance
“…Daily fruit and vegetable consumption drops significantly between the ages of 11 and 15 years among Lithuanian children. These gender and age specific differences are the case among school-aged children in the majority of HBSC countries [3,20,21] and have also been observed in other studies [11,22,23]. These studies demonstrated that older school-aged children tend to consume less fruits and vegetables than younger school children due to growing peer influence and reduced impact of parents [11,23].…”
Section: Discussionsupporting
confidence: 69%
“…Daily fruit and vegetable consumption drops significantly between the ages of 11 and 15 years among Lithuanian children. These gender and age specific differences are the case among school-aged children in the majority of HBSC countries [3,20,21] and have also been observed in other studies [11,22,23]. These studies demonstrated that older school-aged children tend to consume less fruits and vegetables than younger school children due to growing peer influence and reduced impact of parents [11,23].…”
Section: Discussionsupporting
confidence: 69%
“…A breakdown of the outcomes and by whom the interventions were delivered (knowledge syntheses and primary studies) is summarized in Table 5. Some studies had interventions that were delivered by multiple individuals, such as teachers plus another community or school individual (e.g., administrator, health professional, other school personnel, researcher) [21,26,29,37,38,41,52,59,72,97,103-105,118,121,131,134,137,140,144,157,161,198,200,214,217,218,226,249,258,261,274,291,301,309,310,317,338,342]; teachers plus 2 or more other individuals [15,23,28,31,36,43,74,75,88,102,110,119,127,137,159,166,172,175,199,202,205,213,219,246,262,276,299]; Health Department or Ministry of Health together with school administrators or other school personnel [224,264,307]; peers plus teachers and/or administrators [16,30,35,40,55,143,155,190]; administrators and other school personnel [193,297,305]; peers plus other school personnel [55,160]; peers plus administrators plus other school personnel […”
Section: Resultsmentioning
confidence: 99%
“…The aim of the intervention was to increase consumption of fruit and vegetables and intake of fibre, and decrease intake of sugar (Hoppu et al 2010b). Intervention procedures were introduced during an academic year.…”
Section: Results From the Interventionmentioning
confidence: 99%